2010
DOI: 10.1016/j.infbeh.2010.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Interparental relationship dynamics and cardiac vagal functioning in infancy

Abstract: This study examined associations between interparental relationship dynamics and vagus system functioning in infancy. The functioning of the vagus system, part of the parasympathetic nervous system, indexes emotional reactivity and regulation. Interparental avoidance and dyadic adjustment constitute the focus of this study in order to bring attention to relationship dynamics not subsumed under overt conflict. Infants' baseline vagal tone and change in vagal tone in response to a novel toy were assessed at five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 59 publications
1
2
0
1
Order By: Relevance
“…Consistent with conceptual work, empirical studies have reported relations between marital maladjustment, including IPV, and children’s poorer SR (Crockenberg & Langrock, 2001; Davies & Cummings, 1994). Findings also are consistent in showing that adequate interparental relationship adjustment is related to aspects of children’s behavioral and emotional SR, such as higher effortful control, and lower emotional reactivity and higher RSA (e.g., Bridgett et al, 2013; Crockenberg & Langrock, 2001; Davies & Cummings, 1998; Davies, Sturge-Apple, Cicchetti, Manning, & Zale, 2009; Graham, Ablow, & Measelle, 2010; Gustafsson, Cox, & Blair, 2012; Rhoades et al, 2011). Finally, there is evidence that marital conflict affects children’s bottom-up mediated undercontrolled (i.e., impulsivity) and overcontrolled (i.e., behavioral inhibition/fear) SR (see Cummings & Davies, 2002 for discussion).…”
Section: Family Dynamics and Rearing Context As Mechanisms Of Interge...supporting
confidence: 61%
“…Consistent with conceptual work, empirical studies have reported relations between marital maladjustment, including IPV, and children’s poorer SR (Crockenberg & Langrock, 2001; Davies & Cummings, 1994). Findings also are consistent in showing that adequate interparental relationship adjustment is related to aspects of children’s behavioral and emotional SR, such as higher effortful control, and lower emotional reactivity and higher RSA (e.g., Bridgett et al, 2013; Crockenberg & Langrock, 2001; Davies & Cummings, 1998; Davies, Sturge-Apple, Cicchetti, Manning, & Zale, 2009; Graham, Ablow, & Measelle, 2010; Gustafsson, Cox, & Blair, 2012; Rhoades et al, 2011). Finally, there is evidence that marital conflict affects children’s bottom-up mediated undercontrolled (i.e., impulsivity) and overcontrolled (i.e., behavioral inhibition/fear) SR (see Cummings & Davies, 2002 for discussion).…”
Section: Family Dynamics and Rearing Context As Mechanisms Of Interge...supporting
confidence: 61%
“…Second, research has mainly focused on one parent's report of relationship satisfaction (e.g., Graham et al, 2010;Linville et al, 2010). The limited number of studies that have included both mothers and fathers have conceptualised relationship satisfaction at the family-level by either summing or averaging couples' scores (Sturge-Apple et al, 2004) or loading mothers' and fathers' scores onto a single latent construct of couple satisfaction (Kaczynski et al, 2006).…”
Section: Quality Of Interparental Relationship and Child Socioemotion...mentioning
confidence: 99%
“…It is found to be a promotive factor for children’s life satisfaction, interpersonal adjustment, and educational attainment (Brauner-Otto et al, 2020; Jin et al, 2019; Shek, 2000). Affectionate behaviors between parents provide emotional security and role models of interpersonal interactions for children in the early years, which may affect children’s biological response to novel and stressful experiences and have concurrent and long-term implications for their socioemotional development (Davies & Woitach, 2008; Graham et al, 2010; Lucas-Thompson & Clarke-Stewart, 2007). There may also be a positive spillover process in the family where affective interparental interactions influence how parents interact with the child (e.g., parenting, response to children’s characteristics), which indirectly impacts children’s later adjustment (Erel & Burman, 1995; Latham, 2018; Spjeldnes & Choi, 2008; Zhao et al, 2021).…”
Section: Parental Involvement Interparental Affection and Positive De...mentioning
confidence: 99%